Wayfinding Research in Library and Information Studies: State of the Field - Mandel, Lauren H. (Evidence Based Library and Information Practice, 2017)
Objective – Often people enter libraries focused on their primary information needs and haven't considered their need for spatial information to find their way to what they need. This presents unique wayfinding information challenges for libraries. Papers on library wayfinding often include some discussion of the lack of wayfinding research in libraries, but apparently there has been no comprehensive review of the LIS literature on wayfinding.Methods – This paper is a comprehensive review of library wayfinding literature, using the Library, Information Science & Technology Abstracts with Full Text (via EBSCOhost) database to collect the dataset.Results – Findings indicate a small collection of library wayfinding research, primarily focused on academic libraries.Conclusion – Empirical research in this area is limited. Suggestions for future research on library wayfinding, including potential foci for that research, are presented.